2019
DOI: 10.1002/anie.201908060
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrogenation on Cu/Al2O3: Role of the Metal/Support Interface in Driving Activity and Selectivity of a Bifunctional Catalyst

Abstract: Selective hydrogenation of CO2 into methanol is a key sustainable technology, where Cu/Al2O3 prepared by surface organometallic chemistry displays high activity towards CO2 hydrogenation compared to Cu/SiO2, yielding CH3OH, dimethyl ether (DME), and CO. CH3OH formation rate increases due to the metal–oxide interface and involves formate intermediates according to advanced spectroscopy and DFT calculations. Al2O3 promotes the subsequent conversion of CH3OH to DME, showing bifunctional catalysis, but also increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 68 publications
10
75
1
1
Order By: Relevance
“…In terms of required electronic energy, CO 2 cleavage of the adsorbed, bent CO 2 intermediate has a very low energy barrier of +31 kJ mol −1 . This bent CO 2 adsorbate was evaluated previously on several metal carbides 51 and was suggested to enhance the reactivity of CO 2 on interfaces between a metal and a metal carbide 52 or a metal oxide 53 55 . DFT calculations on the clean, Mo-terminated surface of δ-Mo 2 C(001) showed that CO 2 activation on molybdenum carbides is also associated with low activation barriers 56 .…”
Section: Resultsmentioning
confidence: 99%
“…In terms of required electronic energy, CO 2 cleavage of the adsorbed, bent CO 2 intermediate has a very low energy barrier of +31 kJ mol −1 . This bent CO 2 adsorbate was evaluated previously on several metal carbides 51 and was suggested to enhance the reactivity of CO 2 on interfaces between a metal and a metal carbide 52 or a metal oxide 53 55 . DFT calculations on the clean, Mo-terminated surface of δ-Mo 2 C(001) showed that CO 2 activation on molybdenum carbides is also associated with low activation barriers 56 .…”
Section: Resultsmentioning
confidence: 99%
“…S23 †), consistent with the observed formation of dimethyl ether during catalysis. Notably, no formate species on Lewis acidic gallium sites (present in the case of Cu/ZrO 2 , Cu-Zr/ SiO 2 , Cu-Ti/SiO 2 or Cu/Al 2 O 3 systems) 6,17,34,35 are observed, indicating that Ga III Lewis acidic sites possibly favor the subsequent hydrogenation of formate into methoxy species and/or increase the thermodynamic stability of methoxy in comparison to formate species. This is also conrmed by the IR spectra of the ex situ Cu-Ga/SiO 2 sample aer reacting with 1 H 2 / 13 CO 2 (Fig.…”
Section: Catalytic Performance In Co 2 Hydrogenationmentioning
confidence: 99%
“…While formate species are also likely formed as reaction intermediates on Cu-Ga/SiO 2 under reaction condition, the lower stability of formate compared to methoxy would be consistent with (and explains) the higher CH 3 OH selectivity of this material in contrasts to other systems. Indeed, stable formate species have been shown to be able to generate methyl formate that readily decomposes into CO. 6 Further work is needed to investigate the formation (or not) of formate species as key intermediate in this Cu-Ga/SiO 2 system.…”
Section: Catalytic Performance In Co 2 Hydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as catalysts are concerned, efforts have been made to improve the performance of CZA by either replacing/doping Cu with noble metals (e.g., Pt, Pd) [12][13][14][15] or by adding oxides in order to enhance the adsorption properties of the support and to increase the dispersion of the Cu phases [16][17][18][19][20][21]. This is the reason why the majority of studies pinpoint some sort of coupling in the mechanism between the copper phase and the support oxide, with the latter being the anchor point for one of the oxygen atoms of CO 2 [22,23]. In this respect, several promoters have been studied, mainly oxides of metals such as Mn, La, Zr, Cr, and B [21,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%